Implementation of Halal Label as an Intangible Asset on Food and Beverage Business Sustainability - Amrullah, M. Mukhlis; Irianto, Gugus; Adib, Noval (Jurnal Aplikasi Manajemen, 2024)
The majority of the Indonesian population adheres to Islam, and of course, halal food is the most sought-after. Halal labels are increasingly considered important in business due to their positive influence on consumer awareness and the demand for halal products. This study aims to understand how UB Coffee's management interprets the Halal Label as an asset and its implications for business sustainability. This research employs a qualitative method with a case study approach involving UB Coffee's management as the population. Key managers were selected as the sample using purposive sampling, and the data were analyzed descriptively. The results indicate that UB Coffee's management views the Halal Label as valuable and a source of pride, supporting UB Coffee's educational function as part of the educational institution UB and interpreting it as a shared value and commitment. However, UB Coffee has not yet recognized the Halal Label as an asset in its accounting system. The Halal Label has the potential to sustain UB Coffee's business due to the increasing trend of a halal lifestyle. The implications of this study highlight the importance of formally recognizing the Halal Label as an asset to strengthen UB Coffee's long-term business strategy.